East Asian capitalism diversity, continuity, and change - Walter, Andrew, 1961-; Zhang, Xiaoke (Oxford : Oxford University Press, 2012)
This volume analyses developments in East Asian capitalism since the 1980s, focussing on three main areas: business systems financial structures, and labour markets.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Capitalism -- East Asia; East Asia -- Economic conditions -- 20th century; East Asia -- Economic conditions -- 21st century; Labor market -- East Asia